The Lifted Veil - Eliot, George, 1819-1880 (Salt Lake City, UT : Project Gutenberg, 2000)
"The Lifted Veil" by George Eliot is a novella published in 1859. Departing from Eliot's realistic fiction, this Victorian horror tale follows Latimer, a man cursed with the ability to see into the future and read others' thoughts. He becomes obsessed with Bertha, his brother's fiancée, whose mind remains mysteriously closed to him. After marrying her, Latimer discovers dark truths about her nature. The story explores extrasensory perception, fate, and includes a shocking climax involving a blood transfusion experiment that brings the dead momentarily back to life. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Lifted_Veil_(novella)
Release date is 2000-05-01
David Price
Keywords: Psychological fiction; Paranormal fiction